HISTORY OF TRANSLATION OF WORKS OF ALISHER NAVOI INTO FOREIGN LANGUAGES (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article deals with the history of translations of poems and poems of the great Uzbek poet and thinker Alisher Navoi into European languages. The first translation of the poet's poem into German was carried out in 1583 from Italian. Many works were translated from the original. But a significant number of Navoi's poems and poems were translated through Russian. The first Navoi readings and conferences in Europe took place in the winter of 1941 in besieged Leningrad.